Burden of disability in children and adolescents must be integrated into the global health agenda. (17th March 2021) - Cieza, Alarcos; Kamenov, Kaloyan; Sanchez, Mariano Gacto; Chatterji, Somnath; Balasegaram, Mangai; Lincetto, Ornella; Servili, Chiara; Bermejo, Raoul; Ross, David A
Abstract : Alarcos Cieza and colleagues argue that services for children and young people with disability need greater priority